2005
DOI: 10.1111/j.1525-1438.2005.15222.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus plays little role in cervical carcinogenesis in Korean women

Abstract: We examined whether Epstein-Barr virus (EBV) infection plays a role in cervical carcinogenesis in Korean women. EBV infection was examined using polymerase chain reaction (PCR) with two different primer pairs flanking the BamHI "W" fragment of EBV and by EBV-encoded small RNAs (EBER) in situ hybridization in various histologic types of cervical cancer, including 17 cases of squamous cell carcinoma, 36 cases of adenocarcinoma, and 3 cases of small-cell carcinoma. We also evaluated 20 cases of cervical intraepit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…The fact that the EBV/C3d receptor was shown to be expressed in cervical epithelial samples, as well as the clear EBV linkage with epithelium originated tumors, made this hypothesis plausible (15). However, other authors did not reach to the same conclusion, confirming that EBV was acting in cervical tumor pathogenesis (33). The absence of EBV infection in controls and the decline of EBV peak in benign cervical lesions suggest that EBV infection occurs late in cervical oncogenesis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The fact that the EBV/C3d receptor was shown to be expressed in cervical epithelial samples, as well as the clear EBV linkage with epithelium originated tumors, made this hypothesis plausible (15). However, other authors did not reach to the same conclusion, confirming that EBV was acting in cervical tumor pathogenesis (33). The absence of EBV infection in controls and the decline of EBV peak in benign cervical lesions suggest that EBV infection occurs late in cervical oncogenesis.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, there is a continuing need for the identification of viral and host factors that modulate the risk of disease progression (11). Possible agents included Herpes viruses among which more recently Epstein-Barr Virus (EBV), have been suspected to participate in cervical carcinogenesis (15, 33, 31, 13). For example, latent infection with EBV has been shown to act as a carcinogenic cofactor in several epithelial cell malignancies (38).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, most studies exploring and reporting EBV positivity in cervical carcinoma used only PCR-based assays ( 65 , 75 – 78 ). One study reported EBV positivity by PCR in CIN3 lesions and cervical carcinoma in 15 and 5.8%, respectively, while ISH RNA (EBER) revealed no EBV positivity (0%) in any of the tested samples ( 79 ). This led the authors to conclude that EBV plays little role in the pathogenesis of cervical carcinoma in their population ( 79 ).…”
Section: Role Of Ebv In Cervical Cancer: Possible Oncogenic Effects Omentioning
confidence: 99%
“…One study reported EBV positivity by PCR in CIN3 lesions and cervical carcinoma in 15 and 5.8%, respectively, while ISH RNA (EBER) revealed no EBV positivity (0%) in any of the tested samples ( 79 ). This led the authors to conclude that EBV plays little role in the pathogenesis of cervical carcinoma in their population ( 79 ). Similarly, another study reported EBV positivity in 40/58% (69%) of cervical carcinoma samples by PCR while immunohistochemistry (LMP1 protein) revealed EBV positivity in only 26% of tested samples ( n = 23) ( 80 ).…”
Section: Role Of Ebv In Cervical Cancer: Possible Oncogenic Effects Omentioning
confidence: 99%
“…The association of HMSN1 with MS has been reported [45,46,47] and it is possible that the trinucleotide expansion increases susceptibility to epithelial tumours or to EBV. Some suggest a link between cervical cancer and EBV infection [48,49] although this is not fully accepted [50]. …”
Section: Discussionmentioning
confidence: 99%